Perbandingan Teori dan Praktek Sistem Pembelian dan Persediaan Perpetual pada PT. XYZ - Nabilhajid, Haren Penggala; Ahalik, Ahalik (Journal of Emerging Business Management and Entrepreneurship Studies, 2023)
This study aims to provide an understanding to the reader regarding the procedures and accounting records of purchases of goods that occur at PT. XYZ. The analytical method used is descriptive qualitative and quantitative descriptive methods. Data collection methods include interviews with subjects who work at PT. XYZ and document studies to obtain information about the procedures and accounting records of purchases at PT. XYZ. The author sees a combination of learning theory between financial accounting courses and accounting information systems courses in academia in purchasing accounting procedures and records at PT. XYZ. In addition, the authors found a difference between the theory and the practice. The results of this study show that the GAP between learning accounting for purchases in academia and applied is true, but the GAP does not cause a problem because providing theoretical knowledge in academia can make it easier for students to understand purchasing accounting in the field.